26. GENERAL AND DISCHARGE EXPERIENCES OF INPATIENTS AT THE DEPARTMENT OF SURGERY VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL IN 2021 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the general experience and discharge experience of patients at the Surgery Department of Vinmec Times City International General Hospital in 2021 and identify some related factors. Subjects and methods: Cross-sectional description of 228 patients in the Department of Surgery at Vinmec Times City International General Hospital, data collected through an experience assessment toolkit developed by the Medical Quality Research Agency. of American construction. Results: Overall patient experience was 90.4% positive and 9.6% negative. Discharge experiences were 82.5% positive and 17.5% negative. Of these, 11.8% of medical staff provided insufficient information and 6.1% were not provided with information when discharged from the hospital. The overall rating of service quality at very good and good levels is 74.1% and 22.8%, with 86.8% definitely recommending the hospital to family and friends. Some factors related to overall experience: patients with a high school education, never hospitalized, and a hospital stay of less than 2 days had a higher positive experience than other groups. Some factors related to hospital discharge experience: patients under 35 years old, with high school education, never hospitalized and with a hospital stay of less than 2 days have a higher positive experience than other groups. Conclusion: Patients have a very good overall experience when they leave the hospital, but it is necessary to review and find the causes and improve service quality for patients’ less positive experiences.
Keywords: Experience, hospital discharge, positive, patient.